2018
DOI: 10.3389/fphar.2018.01442
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicines Facilitate the Control of Chemotherapy-Induced Side Effects in Colorectal Cancer: Progress and Perspective

Abstract: Side effects, including nausea, vomiting, mucositis, peripheral neuropathy, and diarrhea, have been frequently reported in colorectal cancer (CRC) patients undergoing chemotherapy. Chinese Herbal Medicines (CHMs) display distinct clinical outcomes, as a result, they have been increasingly used as an adjuvant therapy to manage chemotherapy-induced side effects. In this review, we aim to intensively explore the molecular mechanisms of CHMs, underline the significance of CHMs in mitigating the side effects induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 77 publications
0
30
0
Order By: Relevance
“…QC samples were prepared at 11.4, 91.1, and 1166.4 ng/mL for I; 4.9, 39.2, and 501.4 ng/mL for II; 3.9, 31.0, and 397.0 ng/mL for III; 12.4, 98.9, and 1265.6 ng/mL for IV; 9.0, 72.2, and 924.5 ng/mL for V; 5.9, 47.3, and 606.0 ng/mL for VI; 4.7, 37.2, and 476. 4…”
Section: Preparation Of Calibration Standards and Qc Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…QC samples were prepared at 11.4, 91.1, and 1166.4 ng/mL for I; 4.9, 39.2, and 501.4 ng/mL for II; 3.9, 31.0, and 397.0 ng/mL for III; 12.4, 98.9, and 1265.6 ng/mL for IV; 9.0, 72.2, and 924.5 ng/mL for V; 5.9, 47.3, and 606.0 ng/mL for VI; 4.7, 37.2, and 476. 4…”
Section: Preparation Of Calibration Standards and Qc Samplesmentioning
confidence: 99%
“…Cancer is the leading cause of death that seriously threatening the lives of people worldwide [1], and chemotherapy is considered a mainstream treatment for cancer patients. However, chemotherapeutic drugs present several harmful side effects such as cytotoxic effects and host immunosuppression, regardless of treatment efficacy [2–4]. Leucopenia is one of the most common side effects, resulting in reduced resistance and repeated infection, influencing the effects of tumor radiation and chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal medicines (CHMs), including natural compounds and composite formulae derived from a single herb or combination of herbs, have been recognized as complementary adjuvant therapy to diminish chemotherapy-induced side effects and significantly increase overall survival in patients with CRC in China [6,7]. A high intake of natural compounds such as flavonoids, lignans, and isoflavones was correlated with the reduction of CRC risk [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prior works have focused on verifying it. Chen D et al's review [42] reported that Niuche Shenqi Wan were found to display potential therapeutic effects for preventing the genesis and development of CIPN via restoring the slowed blood flow, inhibiting oxidative stress and activating the C fiber. Liu et al's RCT [43] indicated that Guilong Tongluo decoction could delay the onset time of grades 1–4 neurotoxicity (9.4 vs. 6.5 weeks, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%